Pomoc publiczna we Wspólnocie Europejskiej i w Unii Europejskiej w latach 1985–2007 - Rutkiewicz, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The main purpose of this article is to identify and evaluate major diversion of state aid in the European Community and European Union. On this ground there have been formulated proposals for better targeting and using the state aid in Poland in the future. The article includes: comparative analysis of state aid between European Union and Poland, profi le of the area’s support with an indication of the importance of state aid for social and economic development of the European Union. It especially took into consideration the size, forms and allocations of state aid. There have been also evaluated the effectiveness of the actions and effects of state aid established for horizontal, regional and sector aims.
Keywords: pomoc publiczna; Wspólnoty Europejskie; Unia Europejska